STATUS MUTU AIR SUMUR GALI DI WILAYAH KERJA ENAM PUSKESMAS KABUPATEN KULON PROGO - Nur Iswanto; Rina Ernawati; Agnes Dyah Novitasari Lestari; Dewi Rahyuni (Teknik Lingkungan Universitas Islam Indonesia, 2023)
Research has been carried out to test the quality of dug well water on physical, chemical, and biological parameters in the working areas of the Samigaluh I, Girimulyo I, Sentolo I, Pengasih II, Wates, and Galur I Public Health Centers in Kulon Progo Regency. The sample consisted of 60 dug wells with 16 dug wells with low pollution risk based on the results of environmental health inspections and 44 dug wells with moderate pollution risk. the results of the calculation of the pollution index according to the Minister of Health Regulation No. 32 of 2017, of the 60 wells that were sampled for measuring water quality, there were 76.67% wells with lightly polluted water quality status and 23.33% wells with good water quality status. This is in accordance with the estimated risk of pollution based on the location of the well.